Public services in Andalusia in the Almohad era (540 AH-610 AH) (1145 AD-1213 AD) (Journal of the College of Basic Education, 2022)
Summary :Public services are among the basic elements that countries throughout history seek to carry out due to their importance and advancement on the basis of the services they provide. Towards the establishment and establishment of these services in the Andalusian society, such as urban constructions, religious buildings, corners and connections, schools, public libraries, economic services, caesariyas, hotels, and others.